Peran Employee Engagement dalam Mediasi Hubungan antara Work-Life Balance dan Retensi Karyawan Generasi Z di Wilayah Surabaya - Nurul Iman; Elly Yuniar Nitawati (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the role of employee engagement in mediating the relationship between work-life balance and retention of Generation Z employees in the Surabaya area. The research approach used a quantitative method with a mediation regression analysis technique based on EViews software on 180 Generation Z employee respondents in the service and creative industries sectors. The results showed that work-life balance had a positive and significant effect on employee engagement (β = 0.512, p < 0.05) and employee retention (β = 0.348, p < 0.05). However, after employee engagement was included in the model, the direct effect of work-life balance on retention decreased and became insignificant (β = 0.172, p = 0.056). The Sobel test yielded a z-score of 3.94 and a p-value of 0.00008, indicating that employee engagement fully mediated the effect of work-life balance on employee retention. These findings indicate that work-life balance increases retention only when accompanied by high work engagement. This research strengthens the Job Demands–Resources and Social Exchange theories and provides practical implications: organizations need to strengthen a work-life culture that supports employee balance, flexibility, and participation to increase engagement and reduce turnover.